Enhancing Students' Curiosity using e-Atlas PBL Integrated with Yogyakarta's Local Wisdom on Biodiversity Topic - Muhammad Rasyid; Habibatul Unayah; Tien Aminatun; Asri Widowati; Ibrahim Pandu Ame (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
Curiosity is a critical competency in science education, fostering deeper understanding and problem-solving skills. This study aimed to develop and evaluate a problem-based learning (PBL) e-Atlas integrated with Yogyakarta's local wisdom to enhance students' curiosity in biodiversity material. Using the 4-D model (Define, Design, Develop, Disseminate), this research focused on creating an innovative learning tool tailored to address the lack of laboratory resources in schools and promote active learning. The e-Atlas combines interactive digital features with cultural and ecological relevance, enabling students to engage in virtual activities. The product was validated by four experts (media, content, and practitioners), achieving an Aiken's V index of 0.97, categorized as